German economic power in Southeastern Europe: the case of Reemtsma and the Greek tobacco merchants (1923-1939). - Carmona-Zabala, Juan (Taylor & Francis, 2022)
This article explains how the firms involved in tobacco trade between the largest producer and consumer of Oriental-type tobacco (Greece and Germany) adapted their strategies in response to the economic environment of the interwar period, which was characterized by increased economic étatism, high barriers to trade, and generalized economic depression. The leading firm of Germany's cigarette industry Reemtsma adopted innovative strategies for sourcing its raw material, while Greek leaf merchants turned to collective action and political advocacy in response to international competition and labor activism. The history of these strategies exemplifies the interplay between politics and business decisions. It also provides a concrete example of how German economic power over southeastern Europe in the interwar period manifested itself in a specific industry.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5024
Keywords: Tabaco - Comercio - Grecia; Tabaco - Comercio - Alemania; Tobacco; Interwar; Greece; Germany; Business interest associations; International trade; Cartels; Business strategy